Transformasi Peran Profesional Pajak di Era Digitalisasi Perpajakan: Systematic Literature Review - Muhammad Rifansyah; Christina Fransiska; Muhammad Ichsan Diarsyad; Anggara Aulia Himokta (Media Akuntansi Perpajakan, 2026)
This study aims to analyze the transformation of tax professionals’ roles resulting from tax digitalization in Indonesia, particularly the implementation of the Core Tax Administration System. The method used was a Systematic Literature Review employing the SPIDER framework and the PRISMA protocol. A total of 28 articles were selected from 216 identified articles across three academic databases (Google Scholar, Scopus, and SINTA) for the period 2019–2026. The analysis was conducted through thematic synthesis. The findings indicate that digitalization is shifting the role of tax professionals from administrative implementers to data-driven strategic advisors across ten dimensions: primary functions, dominant activities, work patterns, data access, client relationships, relationships with tax authorities, sources of added value, clerical workload, professional risks, and service foundations. Furthermore, the new competencies required include digital hard skills, strategic soft skills, and professional ethics that cannot be replaced by automation. Additionally, the transformation produces a dual impact: increased efficiency and the threat of automation regarding basic compliance tasks. As a result, tax digitalization has transformed the role of tax professionals, not as an existential threat, but as an opportunity to adaptively reposition their roles through digital upskilling and service restructuring, while remaining relevant as a bridge between taxpayers and tax authorities in digitalization era.